Characteristics of fosA-carrying plasmids in E. coli and Klebsiella spp. isolates originating from food and environmental samples. (11th April 2021) - Biggel, Michael; Zurfluh, Katrin; Treier, Andrea; Nüesch-Inderbinen, Magdalena; Stephan, Roger
Abstract: Objectives: Fosfomycin is an important antibiotic for the treatment of MDR Enterobacteriaceae infections. High susceptibility rates are, however, threatened by the spread of plasmids encoding fosfomycin-modifying enzymes. In this study, we sought to characterize the genetic context of fosA in plasmids from Escherichia coli and Klebsiella spp. isolates recovered from food, wastewater and surface water in Switzerland. Methods: E. coli and Klebsiella spp. isolates collected between 2012 and 2019 in Switzerland were screened for fosfomycin resistance. Presence of fosA was verified by PCR and sodium phosphonoformate (PPF) disc potentiation testing, and transferability was tested using conjugation assays. Whole-genome sequences including complete fosA -containing plasmids were determined using long- and short-read sequencing. Results: In 11 E. coli and two Klebsiella spp. isolates, high-level fosfomycin resistance was mediated by plasmids containing fosA3 ( n  = 12) or fosA8 ( n  = 1). Four isolates harboured a near-identical 45 kb IncN plasmid with fosA3, while replicon types varied in the remaining plasmids. The fosA genes were typically embedded in IS 26 -bounded transposition units and frequently located in the proximity of bla CTX-M transposition units. Conclusions: Although fosfomycin resistance rates are currently low, the presence of fosA -encoding plasmids circulating in the Enterobacteriaceae population suggests that fosfomycin resistance may rapidly spread upon increased selection pressure. Transposition mobility of fosA and co-location on plasmids with other resistance genes may further promote its dissemination.